Gender tool to promote women’s innovation - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
CIP-Papa Andina has developed a tool to more fully integrate gender and women’s participation in innovation-promoting methodologies. The tool is comprised of guidelines with practical recommendations for mainstreaming gender into innovation promoting methodologies, thus converting strategy into practice. The tool is aimed at promoting equal benefits for men and women from pro-poor innovations.